Comparative performance of growth, flowering behaviour and fruit development traits in parental lines of bitter gourd (Momordica charantia L.) cv. Pusa Hybrid-1 - G. S. JAT; BALRAJ SINGH; B. S. TOMAR; HANUMAN RAM (Seed Research, 2026)
The present investigation on parental lines of bitter gourd (Momordica charantia L.) cv. Pusa hybrid-1 was carried out at CPCT farm ICAR-IARI, New Delhi during the summer season of 2010 under insect proof net (IPN) and open field condition (OFC). The female line (seed parent) and male parent (pollen parent) were transplanted in block method following the planting ratio of 3:1, under drip fertigation in IPN and OFC. Significantly higher vine length, number of leaf node on 30 & 45 days from transplanting (DFT) and inter nodal length were recorded in seed and pollen parent under IPN as compared to OFC. The time taken for opening of first female and male flower in seed parent and pollen parent (55.40 days and 51.10 days respectively) were significantly lower under IPN. The production of female flower (31.10/plant) and male flower (40.10/plant) were significantly higher under IPN as compared to OFC. The number of fruit set (3.00) and matured fruit (2.90/plant was significantly higher under IPN than OFC (1.80 and 1.30 respectively). The overall percentage of fruit set and duration of fruit set under IPN was significantly higher than the OFC. The fruit development attributes i.e. fruit weight & fruit length was significantly higher in IPN, where as non-significant difference for fruit width and flesh thickness was recorded in cross fruits under both the conditions. The incidence of virus and insect pests was negligible or very low under IPN, whereas 54% plants were affected at maturity by virus, under OFC.